Development of Solar Powered Electronic Shipping Container Locking System - Ishak, Ahmad Radzi Khalis; Mohamad , Khairul Anuar (Evolution in Electrical and Electronic Engineering, 2021)
In recent years, an electronic locking system has developed that utilizes technology that enables the consumer to unlock the locking system via a keyless or smart device in person or remotely, as well as to track the usage of the locking system via notification. However, the usage of the electronic container locking device has been slowed down because the system needs a continuous supply of electricity. The Solar Powered Electronic Locking Device is also one of the options for a continuous power supply to the locking system.